Identifying optimal Window-To-Wall Ratio (WWR) and Window-To-Floor Ratio (WFR) for typical higher educational classrooms to address deficiencies in daylighting design - Wan Abdullah, Wan Nur Hanani; Abdul Tharim, Asniza Hamimi; Ismail, Asmat; Ibrahim, Farah Salwati; Wan Mohammad, Wan Nur Syazwani (Universiti Teknologi MARA, Perak, 2025)
Daylighting plays a crucial role in creating conducive learning environments in higher education classrooms, enhancing visual comfort, student performance, well-being, and overall satisfaction. However, many educational facilities suffer from poor daylighting design, leading to uneven illumination, glare, and overdependence on artificial lighting. This study addresses these issues by investigating current daylighting conditions, particularly focusing on Window-to-Wall Ratio (WWR) and Window-to-Floor Ratio (WFR), which significantly influence natural light distribution. The research aims to assess the effectiveness of existing glazing configurations and propose optimised WWR and WFR values using both field measurements and simulation through Building Information Modelling (BIM) software, specifically Autodesk Revit. Field data from two classrooms equipped with tinted glass were compared to daylight factor (DF) standards from MS1525 (2019) and WFR recommendations of UBBL (1984). Findings reveal that while WWR and WFR exceeded the minimum threshold of 20%, daylight penetration, and uniformity varied, with some areas suffering from insufficient light and glare. This research highlights the need for improved daylighting design, offering evidence-based recommendations to optimize natural light in educational spaces, enhancing comfort and energy efficiency.